Influence of Clonidine on Antihypertensive Selective Afferent Vagal Nerve Stimulation in Rats. Issue 6 (27th June 2016) - Gierthmuehlen, Mortimer; Aguirre, Debora; Cota, Oscar; Zentner, Josef; Stieglitz, Thomas; Plachta, Dennis T. T.
Abstract : Objective: Selective‐afferent vagal nerve stimulation (sVNS) may be a treatment option for therapy‐resistant hypertension, as it lowers blood pressure (BP) in rats without causing significant side effects. Alpha‐2‐agonists are widely used for the treatment of withdrawal, chronic pain and other disorders, and even if sVNS becomes a treatment option for therapy resistant hypertension, in some patients it might be necessary to combine sVNS with an alpha‐2‐agonist like clonidine. Alpha‐2‐agonists exhibit a central and peripheral mechanism of action. This study investigated the influence of the commonly used alpha‐2‐agonist clonidine on sVNS. Materials and Methods: A polyimide multichannel‐cuff‐electrode was placed around the left vagal nerve bundle including the aortic depressor nerve (ADN) in eight male Wistar rats for the focused stimulation of baroreceptive fibers of the ADN. Stimulation parameters were adapted to the thresholds of the individual animals and ranged from frequencies between 30 and 50 Hz, amplitudes of 0.5–0.9 mA and pulse widths between 0.4 and 0.8 ms. BP was recorded using a microtip transducer in the left carotid artery, and electrocardiography was registered using subcutaneous needle electrodes. Results: Before clonidine, we found a frequency‐dependent drop of BP with maximum at 40 Hz. The animals' mean arterial blood pressures and respiration rate dropped after intravenous clonidine administration (10 µg/kg bodyweight), and sVNS still decreased in BP, but they did so to a lesser extent. Unwanted bradycardia, which was expected by the superimposition of sVNS and clonidine, did not occur. Left‐sided vagotomy abolished the respiratory depressant effect of clonidine and blunted the BP reducing effect of sVNS while sVNS hardly affected heart rate anymore. Conclusions: The effect of sVNS on BP is dampened by clonidine, but sVNS can still lower the BP in clonidine treated rats without causing significant bradycardia.